2021
DOI: 10.1017/s1049023x21001187
|View full text |Cite
|
Sign up to set email alerts
|

A Change from a Spinal Immobilization to a Spinal Motion Restriction Protocol was Not Associated with an Increase in Disabling Spinal Cord Injuries

Abstract: Background:Over the past decade, Emergency Medical Service (EMS) systems decreased backboard use as they transition from spinal immobilization (SI) protocols to spinal motion restriction (SMR) protocols. Since this change, no study has examined its effect on the neurologic outcomes of patients with spine injuries.Objectives:The object of this study is to determine if a state-wide protocol change from an SI to an SMR protocol had an effect on the incidence of disabling spinal cord injuries.Methods:This was a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…61 In the United States, EMS systems that studied their own progression from immobilization protocols to SMR protocols did not see any increase in disabling spinal injuries in their patients with a transition to SMR protocols. 62 Recommendation: We suggest SCP should be considered an appropriate goal in patients with actual or suspected spinal injury; current evidence suggests SMR and not immobilization is the safest and most effective means of SCP. Weak recommendation, low-quality evidence.…”
Section: Effectiveness Of Spinal Immobilization In Reducing the Incid...mentioning
confidence: 99%
See 1 more Smart Citation
“…61 In the United States, EMS systems that studied their own progression from immobilization protocols to SMR protocols did not see any increase in disabling spinal injuries in their patients with a transition to SMR protocols. 62 Recommendation: We suggest SCP should be considered an appropriate goal in patients with actual or suspected spinal injury; current evidence suggests SMR and not immobilization is the safest and most effective means of SCP. Weak recommendation, low-quality evidence.…”
Section: Effectiveness Of Spinal Immobilization In Reducing the Incid...mentioning
confidence: 99%
“…In the United States, EMS systems that studied their own progression from immobilization protocols to SMR protocols did not see any increase in disabling spinal injuries in their patients with a transition to SMR protocols. 62…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Additional research has examined patient characteristics and outcomes after introducing new guidelines, observing not only substantial undertreatment among patients who met criteria for precautions but also increases in the number of patients with confirmed injuries who received no treatment from emergency medical services (EMS) 20,21 . While a small number of additional studies using high‐level population data have observed no increase in a final diagnosis of spinal cord injury after SMR, 22,23 the prospects of variable practice, ineffective interventions, and patients not receiving the treatment intended for their injury remain a concern.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of semi-rigid collars has been questioned by Clemency et al (2021) and Hawkridge et al's (2020) systematic review found that most studies disagreed with spinal collars prehospital. Oosterwold et al (2017) identified potential issues with immobilisation as nausea/vomiting, pain, shortness of breath and combativeness/anxiety.…”
Section: Introductionmentioning
confidence: 99%